Microwave-assisted hydrodistillation of essential oil of Cúrcuma longa (rhizomes): response surface optimization - Cano-Botero, José Leonardo; Ospina-Balvuena, Yeferson; Gutiérrez-Cifuentes, Jorge Andrés; Ríos-Vásquez, Eunice (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The properties of the plants of the Zingiberaceae family are widely known worldwide, in traditional medicine, as anti-inflammatory, antioxidant, antiviral, among others. Framed in the high biochemical value of this family, this research focused on the optimization of extracting essential oils method from Curcuma longa dry rhizomes collected in the Department of Quindío (Colombia), using microwave-assisted hydrodistillation and evaluating variables optimized by response surfaces. The results obtained from the optimization showed a considerable improvement in the oils extraction from some aspects and variables, compared to conventional hydrodistillation. The yield of essential increased by 32%, in α-Turmerone as the most abundant component there was by 31%, the extraction time was reduced from 120 to 59 minutes, and the energy consumption and CO2 emission were reduced by one third. These interesting results encourage the potential improvement of possible applications in health, food or cosmetics.